John Buckley and John O’Flynn (eds), Ceol Phádraig: Music at St Patrick’s College Drumcondra 1875–2016 (2019) - McCarthy, Marie (Journal of the Society for Musicology in Ireland, 2020)
A review of John Buckley and John O’Flynn (eds), Ceol Phádraig: Music at St Patrick’s College Drumcondra 1875–2016 (Dublin: Carysfort Press, & Oxford, UK: Peter Lang, 2019). ISBN 978-1-78997-579-6